(3TQM GdhQbGJ aj CUhd Gdabgs - (3CHh YeQh Hf GdUdGMs; (3CHj GdeYGdj YHO Gdedc Hf YHO Gddg Hf jhSa GdLhjfj, EeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh YeQh Hf GdUdGM CeG HYO MeO Gddg aEfi JhLgJ Edi ETGQI cQjeI HJYdjb Ydi cJGH GdhQbGJ ai CUhd Gdabg GdefShH Edi GdYdGeI EeGe GdMQejf hebJVi GdbUO GdhQbGJ LeY hQbI s
(3BNQgG (B:s
(3ef MOjK YeQh Hf GdYGU QVi Gddg Yfg hdaXg ai GdUMjM (B( (3EPG GLJgO GdMGce aMce aCSGH adg CLQGf hEPG Mce aCNWC adg CLQ (B) (3hGddg CYde Je GdcJGH HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(1697) s
Keywords: (3CUhd Gdabgs